Company Financial Report Analysis: Case Study of PT Pakuwon Jati Tbk - Sinurat, Mangasi (Sekolah Tinggi Ilmu Ekonomi Bina Karya, 2024)
This article aims to analyze the financial ratios of PT Pakuwon Jati Tbk during the 2023 period in order to evaluate the company's financial performance. The financial ratios used include liquidity, solvency, profitability, activity, market and dividend policy ratios. The results of the analysis show that PT Pakuwon Jati Tbk has a stable level of liquidity, the company's solvency shows low dependence on debt, In terms of profitability, PWON shows efficiency in cost management and the ability to generate competitive profits. However, there are variations in asset management efficiency; the company needs to improve inventory management, although receivables collection is carried out well. From a market perspective, the company shows attractive profits for investors, Finally, a conservative dividend policy reflects the company's strategy to retain most of the profits for reinvestment in expansion projects.